Universal Algorithm for Generation of Matrices Used in Dynamics of Circular Thimoshenko Segments - Olszowski, B. (Engineering Transactions, 1992)
The paper deals with a numerical generation of the basic solutions for a set of ordinary differential equations governing the plane vibration of a circular Timoshenko segment and having the normal Cauchy’s form. The generation algorithm arose as further development of author’s method described in [1] and enables to analyse the stationary harmonic motion of the segment for any boundary conditions and arbitrary values of physical parameters. Numerical calculations are restricted to the analysis of simply supported segments only. For testing purposes, however, this analysis is performed for three types of models: Rayleigh-Timoshenko (RT) and Bernoulli - Euler models with extensible (BEe) or inextensible (BEi) axis. The results of eigenfrequency calculations are plotted and tabulated.